1994
DOI: 10.1002/jsfa.2740660220
|View full text |Cite
|
Sign up to set email alerts
|

Correlations among quality parameters of peach fruit

Abstract: The correlations among quality parameters of peach fruit (Prunus persica L Batsch) were studied for eight different cultivar-shape-site-nitrogenseason combinations ('treatments'). Between 66 and 183 fruits were taken from each treatment and the quality parameters of skin colour, flesh firmness and taste were measured. Differences and similarities between treatments were analysed using a recent development in biplot multivariate analysis: the ACT method (Analyse Conjointe de Tableaux), which allows the study of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 18 publications
4
17
0
1
Order By: Relevance
“…However, the coefficient correlations were not sufficiently high to prove this relationship. On the other hand, there was no relationship between colour and firmness or taste (Table 5), in agreement with previous work in peach (Génard et al 1994).…”
Section: Evaluation Of Chemical and Sensory Attributessupporting
confidence: 93%
See 1 more Smart Citation
“…However, the coefficient correlations were not sufficiently high to prove this relationship. On the other hand, there was no relationship between colour and firmness or taste (Table 5), in agreement with previous work in peach (Génard et al 1994).…”
Section: Evaluation Of Chemical and Sensory Attributessupporting
confidence: 93%
“…In this sense, multivariate analysis is a useful tool which has been used to establish genetic relationship among cultivars and to study correlations among variables (Hilling and Iezzoni 1988;Brown and Walker 1990;Iezzoni and Pritts 1991;Génard and Bruchou 1992;Pérez-González et al 1993;Esti et al 1997;Badenes et al 1998;Gurrieri et al 2001). Studies carried out in peach (Byrne et al 1991;Génard and Bruchou 1992;Génard et al 1994;Esti et al 1997) have found correlations among some pomological traits. However, we did not find specific reports for apricot concerning the relationships among fruit quality parameters, and only a few studies have included the relationships between certain pomological traits (Pérez-González 1992;Badenes et al 1998;Gurrieri et al 2001;Asma and Ozturk 2005).…”
Section: Introductionmentioning
confidence: 97%
“…Endocarp staining can be an appreciated trait by specific consumers although a relationship of this trait with postharvest browning has also been reported (Ogundiwin et al 2009). No relationship between skin colour and firmness was found for any cross which is in agreement with previous work in peach (Génard et al 1994) and apricot (Ruiz and Egea 2008). In general, fruit weight was positively correlated with annual yield, endocarp staining, pH, RI, firmness and sphericity, and negatively correlated with skin blush and TA.…”
Section: Cross Influence On Agronomic and Fruit Quality Traitssupporting
confidence: 91%
“…The quality parameters may not be independent of each other, and therefore, relationships among them should be studied to improve the choice of production objectives. Previous studies carried out in peach (Byrne et al 1991;Génard et al 1994;Esti et al 1997;Génard et al 1999) have found correlations among some pomological traits related to the fruit quality.…”
Section: Introductionmentioning
confidence: 98%
“…Génard et al (1991) ont montré qu'elle dépendait du niveau de croissance du fruit : les fruits ayant une croissance longue et importante sont les plus sucrés et les moins acides. En outre, les variations des teneurs en sucres et en acides ne sont pas indépen-dantes car il y a, à maturité, une corrélation positive entre le saccharose et l'acide malique, et une corrélation négative entre ces constituants et l'acide citrique (Génard et al 1994). Les travaux de Pavel et DeJong (1993) montrent que la composition du fruit varie avec les phases de croissance et leur intensité.…”
unclassified